Discourse on the Role of Victim Advocates in the Concept of Plea Bargaining: Towards Restorative Justice? - Suindrayani, Ni Putu Tya; Putra, Rahmat Angga Dwi; Fratama, Tomi Agi; Pa, Putri Mega Silvia (Faculty of Law, Udayana University, 2025)
The purpose of this research is to examine how the discourse on the role of victim advocates in the concept of plea bargaining as an attempt to achieve restorative justice in the adjudication of criminal cases in Indonesia. The methodology used is qualitative research with a non-doctrinal normative legal research method, as well as a regulatory and conceptual approach. The results of this study reveal a discourse on the situation of victim advocates in the current Indonesian criminal justice system, followed by a critical review of the concept of plea bargaining in the criminal justice system, and attempts to achieve restorative justice for victims by strengthening the role of victim advocates through its implementation in the concept of plea bargaining. Thus, the concept of plea bargaining not only prioritizes the interests of the defendant, but also serves as an alternative pathway to achieve recovery for victims of crime.